Empowering Children with Healthy Internet Literacy and Digital Content Creation Skills - Heribertus Ary Setyadi; Galih Setiawan Nurohim; Wawan Haryanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Children development in the digital era confronts substantial challenges stemming from rapid technological advancements. Children of the current generation, specifically Gen Z and Post Gen Z, are immersed in digital technology from a young age. Early childhood represents a demographic highly susceptible to the detrimental influences of digital media. Consequently, it is imperative to ensure that digital media utilized in early childhood education not only effectively fosters children's skills and knowledge but also remains secure and avoids producing adverse outcomes. This community service project purpose is to provide children with healthy internet literacy and to conduct training on creating digital content for them. This activity's focus was on managers and children of Mizan Amanah Orphanage for Orphans and the Poor in Surakarta. Asset-Based Community Development (ABCD) approach was utilized, with the goal community empowering by leveraging its inherent potential and resources. Implementation phases involved a needs assessment (Discovery), defining aspirations (Dream), creating the training module (Design), finalizing a plan through a Focus Group Discussion (Define), and executing the training (Destiny). The processed questionnaires from all participants concluded that workshop material was highly beneficial and tutor's delivery was satisfactory. 63% of participants were satisfied, and 32% were very satisfied.